2021
DOI: 10.1111/epi.16959
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery in infants up to 3 months of age: Safety, feasibility, and outcomes: A multicenter, multinational study

Abstract: Summary Objective Drug‐resistant epilepsy (DRE) during the first few months of life is challenging and necessitates aggressive treatment, including surgery. Because the most common causes of DRE in infancy are related to extensive developmental anomalies, surgery often entails extensive tissue resections or disconnection. The literature on “ultra‐early” epilepsy surgery is sparse, with limited data concerning efficacy controlling the seizures, and safety. The current study's goal is to review the safety and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 51 publications
(88 reference statements)
4
50
0
Order By: Relevance
“…Of the remaining 214 studies the full text was assessed for the inclusion criteria mentioned above. Only 14 were included [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In addition, two more articles were discovered by assessing the references of the reviewed articles [41,42].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 214 studies the full text was assessed for the inclusion criteria mentioned above. Only 14 were included [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In addition, two more articles were discovered by assessing the references of the reviewed articles [41,42].…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, two more articles were discovered by assessing the references of the reviewed articles [41,42]. In total, four studies strictly reported on outcomes after epilepsy surgery in infants below the age of six months [27,29,32,33]. All studies were retrospective.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative and largely unknown complications of an early intervention should be weighed against the risk of life-long developmental drawbacks of ongoing detrimental epilepsy and/or anticonvulsant therapy. However, early epilepsy surgery in infancy is receiving increased attention (10,11). First results are promising with seizure freedom ranging from 66 to 82.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of multiple antiseizure medications was also negatively associated with longitudinal CVI outcome, and suggests that Practically, it is important for the vision care provider to consider the number of seizure medications and whether if it may be affecting the child's performance during a CVI vision assessment. This would importantly pair up with the increasing tendency toward early aggressive seizure/epilepsy management among neurologists, including offering earlier curative or palliative epilepsy surgery options and few medication trials (Prideaux et al, 2018;Roth et al, 2021;Perry et al, 2022).…”
Section: Epilepsymentioning
confidence: 99%